2020
DOI: 10.1099/jmm.0.001092
|View full text |Cite
|
Sign up to set email alerts
|

Same-day antimicrobial susceptibility test using acoustic-enhanced flow cytometry visualized with supervised machine learning

Abstract: Purpose. Antimicrobial susceptibility is slow to determine, taking several days to fully impact treatment. This proof-of-concept study assessed the feasibility of using machine-learning techniques for analysis of data produced by the flow cytometer-assisted antimicrobial susceptibility test (FAST) method we developed. Methods. We used machine learning to assess the effect of antimicrobial agents on bacteria, comparing FAST results with broth microdilution (BMD) antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The international standard operating procedure, regulatory guidelines, and quality assurance for using the WGS method for AMR surveillance are not currently available[ 198 ]. AI offers to improve the limitations of the previous technologies'[ 201 203 ].The success of AI depends on the comprehensiveness of data and the quality of databases containing the big clinical data[ 194 , 204 ]. The challenges of obtaining evidence-based AMR surveillance remain the lack of standardized data and periodic updates[ 194 , 205 207 ].…”
Section: Discussionmentioning
confidence: 99%
“…The international standard operating procedure, regulatory guidelines, and quality assurance for using the WGS method for AMR surveillance are not currently available[ 198 ]. AI offers to improve the limitations of the previous technologies'[ 201 203 ].The success of AI depends on the comprehensiveness of data and the quality of databases containing the big clinical data[ 194 , 204 ]. The challenges of obtaining evidence-based AMR surveillance remain the lack of standardized data and periodic updates[ 194 , 205 207 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, differentiation between antimicrobial exposed and unexposed populations has proved difficult and new approaches such as adaptive multi-dimensional statistics have been developed 17 . An assay for carbapenem resistance has been developed that uses acoustic-focusing flow cytometry to deliver a rapid S/R classification together with a quantitative MIC in ~2 h from a clinical isolate 18 , 19 . Flentie et al 20 introduced a novel assay that measured bacterial concentrations by binding a small-molecule amplifier to the bacterial surface.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the goal of most of these models is microorganism identification/quantification and evaluation of antimicrobial resistance with the purpose of reducing the turnaround time. As an example, Inglis et al demonstrated that supervised machine learning could expedite the identification of antimicrobial resistance by using data generated through flow-cytometer-assisted antimicrobial susceptibility testing [ 30 ]. Their prototype was able to generate a predictive inhibitory concentration within 3 h of identification of a positive blood culture, where standard methods take approximately 24 h after culture positivity.…”
Section: During Antimicrobial Therapymentioning
confidence: 99%